Composition and Antioxidant, Antienzymatic and Antimicrobial Activities of Volatile Molecules from Spanish Salvia lavandulifolia (Vahl) Essential Oils - Ana-Belen Cutillas; Alejandro Carrasco; Ramiro Martinez-Gutierrez; Virginia Tomas; Jose Tudela (Molecules, 2017)
The current study describes the composition of Salvia lavandulifolia (Vahl) essential oils (SlEOs) obtained from plants cultivated in Murcia (Spain), as determined by gas chromatography. Relative and absolute concentrations, the enantiomeric ratios of chiral compounds and the in vitro antioxidant, antienzymatic and antimicrobial activities are described. The main components of the SlEOs were camphor, 1,8-cineole, camphene and α-pinene, and the main enantiomers were (+)-camphor and (−)-camphene. The activities against free radicals and the capacity to reduce and chelate metallic ions were measured. SlEO-3 showed the highest activity in ORAC, DPPH, ABTS and reducing power methods, while SlEO-1 exhibited the highest chelating power. The activity of lipoxygenase and acetylcholinesterase could be inhibited by all the SlEOs, being bornyl acetate and limonene the most active individual compounds against lipoxygenase and 1,8-cineole against acetylcholinesterase. SlEOs and some individual compounds inhibited Escherichia coli, Staphylococcus aureus and Candida albicans. These results increase our knowledge of SlEOs and, particularly, provide for the first time a complete characterization of SlEOs from Murcia, Spain, while proposing possible biotechnological uses for them.